GaN-based blue-green light LED epitaxial structure and preparation method thereof
By introducing periodically alternating AlN layer and GaN layer stress release layer into the multi-quantum well layer of GaN-based blue-green light LED, the polarization problem caused by lattice mismatch is solved, the luminous efficiency is improved, and the Droop effect is reduced.
Patent Information
- Application Number
- CN202510015352.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-25
AI Technical Summary
In the multi-quantum well layer of GaN-based blue-green LED, the lattice mismatch between the InGaN-potential well layer and the GaN barrier layer is severely, resulting in more serious piezoelectric polarization and electron hole separation, affecting luminescence efficiency.
The multi-quantum well layer structure is adopted, including shallow well transition layer, high-temperature quantum well layer, stress relief layer and low-temperature quantum well layer. The stress relief layer is composed of AlN layer and GaN layer stacked periodically alternately. The stress relief layer reduces epitaxial defects, reduces polarization electric field, and improves the electron hole recombination efficiency.
It effectively reduces the Droop effect of GaN-based blue-green LED under high current and improves the luminous efficiency.
Smart Images

Figure CN119894184A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of semiconductor technology, and in particular to a GaN-based blue-green light LED epitaxial structure and a preparation method thereof. Background Art
[0002] The multi-quantum well layer of GaN-based blue-green LED is generally composed of a periodic stack of InGaN potential well layer and GaN barrier layer, in which the In component content of the InGaN potential well layer is 0.15-0.3. The growth temperature of the InGaN potential well layer with a high In component is lower and there are more defects. The periodic stacking of the InGaN potential well layer and the GaN barrier layer leads to the accumulation of defects, and the lattice quality is further reduced, which seriously affects the luminous efficiency of the GaN-based blue-green LED. In addition, the lattice mismatch of the InGaN potential well layer and the GaN barrier layer with a high In component is serious, which leads to more serious piezoelectric polarization of the multi-quantum well layer, and the separation of electrons and holes in space, which seriously affects the luminous efficiency of the GaN-based blue-green LED. Summary of the invention
[0003] The technical problem to be solved by the present invention is to provide a GaN-based blue-green light LED epitaxial structure and a preparation method thereof, which can improve the luminous efficiency of the GaN-based blue-green light LED under high current density.
[0004] In order to solve the above problems, the present invention discloses a GaN-based blue-green light LED epitaxial structure, comprising a substrate and a buffer layer, a 3D layer, a U-GaN layer, an N-GaN layer, a multi-quantum well layer, an electron blocking layer and a P-GaN layer stacked in sequence on the substrate; wherein the multi-quantum well layer comprises a shallow well transition layer, a high-temperature quantum well layer, a stress release layer and a low-temperature quantum well layer stacked in sequence, and the stress release layer comprises AlN layers and GaN layers stacked alternately in a periodic manner.
[0005] As an improvement of the above technical solution, the number of cycles of the alternating growth of the stress release layer is 2 to 10, the thickness of the AlN layer is 1 nm to 10 nm, and the thickness of the GaN layer is 1 nm to 10 nm.
[0006] As an improvement of the above technical solution, the GaN layer is a Si-doped GaN layer, and the Si doping concentration is 1×10 16 atoms / cm 3 ~1×10 19 atoms / cm 3 .
[0007] As an improvement of the above technical solution, the shallow well transition layer includes periodically alternately stacked In x Ga 1-x N potential well layer and a first GaN barrier layer; the high temperature quantum well layer includes periodically alternately stacked Iny Ga 1-y N potential well layer and a second GaN barrier layer; the low temperature quantum well layer comprises periodically alternately stacked In z Ga 1-z N potential well layer and a third GaN barrier layer; wherein 0.01≤x≤y≤z≤0.5.
[0008] As an improvement of the above technical solution, the number of cycles of the alternating growth of the shallow well transition layer is 1 to 20, and the In x Ga 1-x The In component ratio x of the N potential well layer is 0.01-0.1, and the thickness is 1nm-5nm. The first GaN barrier layer is a Si-doped GaN barrier layer, and the Si doping concentration is 5×10 17 atoms / cm 3 ~5×10 19 atoms / cm 3 , thickness is 10nm~50nm;
[0009] The number of cycles of the alternating growth of the high temperature quantum well layer is 1 to 20. y Ga 1-y The In component ratio y of the N potential well layer is 0.1-0.2, and the thickness is 1nm-5nm. The second GaN barrier layer is a Si-doped GaN barrier layer, and the Si doping concentration is 5×10 16 atoms / cm 3 ~5×10 18 atoms / cm 3 , thickness is 5nm~30nm;
[0010] The number of cycles of the alternating growth of the low temperature quantum well layer is 6 to 20. z Ga 1-z The In component ratio z of the N potential well layer is 0.2-0.5, and the thickness is 2nm-5nm. The third GaN barrier layer is a Si-doped GaN barrier layer, and the Si doping concentration is 1×10 17 atoms / cm 3 ~5×10 18 atoms / cm 3 , thickness is 5nm~20nm.
[0011] As an improvement of the above technical solution, it also includes a hole injection layer and / or a contact layer;
[0012] The hole injection layer is arranged between the low-temperature quantum well layer and the electron blocking layer; the hole injection layer is a low-temperature P-GaN layer with a thickness of 10nm to 100nm and a Mg doping concentration of 1×10 18 atoms / cm3 ~1×10 21 atoms / cm 3 ;
[0013] The contact layer is disposed on the P-GaN layer; the contact layer is a heavily doped P-GaN layer with a thickness of 1nm to 20nm and a Mg doping concentration of 1×10 18 atoms / cm 3 ~1×10 22 atoms / cm 3 .
[0014] Correspondingly, the present invention also discloses a method for preparing a GaN-based blue-green light LED epitaxial structure, which is used to prepare the above-mentioned GaN-based blue-green light LED epitaxial structure, comprising the following steps:
[0015] Providing a substrate, and sequentially growing a buffer layer, a 3D layer, a U-GaN layer, an N-GaN layer, a multi-quantum well layer, an electron blocking layer, and a P-GaN layer on the substrate;
[0016] The multi-quantum well layer comprises a shallow well transition layer, a high-temperature quantum well layer, a stress release layer and a low-temperature quantum well layer stacked in sequence, and the stress release layer comprises an AlN layer and a GaN layer stacked alternately in a periodic manner.
[0017] As an improvement of the above technical solution, the growth temperature of the stress release layer is 700° C. to 950° C., the growth pressure is 100 torr to 500 torr, and the V / III ratio is 2000 to 20000.
[0018] As an improvement of the above technical solution, the preparation method of the shallow well transition layer includes periodically alternating the growth of In x Ga 1-x N potential well layer and the first GaN barrier layer, the In x Ga 1-x The growth temperature of the N potential well layer is 750° C. to 950° C., the growth pressure is 100 torr to 500 torr, and the V / III ratio is 500 to 10000; the growth temperature of the first GaN barrier layer is 750° C. to 950° C., the growth pressure is 100 torr to 500 torr, and the V / III ratio is 500 to 10000;
[0019] The preparation method of the high temperature quantum well layer comprises periodically alternatingly growing In y Ga 1-y N potential well layer and the second GaN barrier layer, the In y Ga 1-yThe growth temperature of the N potential well layer is 750° C. to 950° C., the growth pressure is 100 torr to 500 torr, and the V / III ratio is 2000 to 20000; the growth temperature of the second GaN barrier layer is 750° C. to 1000° C., the growth pressure is 100 torr to 500 torr, and the V / III ratio is 2000 to 20000;
[0020] The preparation method of the low temperature quantum well layer comprises periodically alternatingly growing In z Ga 1-z N potential well layer and the third GaN barrier layer, the In z Ga 1-z The growth temperature of the N potential well layer is 700℃~850℃, the growth pressure is 100torr~500torr, and the V / III ratio is 2000~20000; the growth temperature of the third GaN barrier layer is 800℃~950℃, the growth pressure is 100torr~500torr, and the V / III ratio is 2000~20000.
[0021] As an improvement of the above technical solution, it also includes growing a hole injection layer between the multi-quantum well layer and the electron blocking layer, and / or growing a contact layer on the P-GaN layer;
[0022] The hole injection layer has a growth temperature of 650°C to 850°C, a growth pressure of 100 torr to 500 torr, and a V / III ratio of 500 to 10000;
[0023] The growth temperature of the contact layer is 650° C. to 950° C., the growth pressure is 100 torr to 500 torr, and the V / III ratio is 10,000 to 20,000.
[0024] The implementation of the present invention has the following beneficial effects:
[0025] In the epitaxial structure of the GaN-based blue-green light-emitting diode of the present invention, the multi-quantum well layer includes a shallow well transition layer, a high-temperature quantum well layer and a low-temperature quantum well layer stacked in sequence, and a stress release layer is inserted between the high-temperature quantum well layer and the low-temperature quantum well layer, which is a periodic structure, and each period includes an AlN layer and a GaN layer stacked in sequence. Through the stress release layer, the epitaxial defects caused by the high-temperature quantum well layer can be effectively reduced, the GaN epitaxial dislocation density is reduced, the surface morphology of the GaN epitaxial layer is improved, the epitaxial stress is released, and the polarization electric field of the low-temperature quantum well layer grown later is effectively reduced, thereby reducing the overflow of electrons under large currents, and improving the luminous efficiency of the light-emitting diode under large currents, that is, reducing the Droop effect of the light-emitting diode. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1It is a structural schematic diagram of a GaN-based blue-green LED epitaxial structure provided by an embodiment of the present invention;
[0027] Figure 2 is a schematic structural diagram of a GaN-based blue-green LED epitaxial structure provided by another embodiment of the present invention;
[0028] Figure 3 This is a schematic diagram of the structure of a multi-quantum well layer of a GaN-based blue-green LED epitaxial structure provided by an embodiment of the present invention;
[0029] Figure 4 It is a flow chart of a method for preparing a GaN-based blue-green light LED epitaxial structure provided by one embodiment of the present invention. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in further detail below.
[0031] like Figure 1 and Figure 3 As shown, the present invention discloses a GaN-based blue-green LED epitaxial structure, comprising a substrate 1 and a buffer layer 2, a 3D layer 3, a U-GaN layer 4, an N-GaN layer 5, a multi-quantum well layer 6, an electron blocking layer 7 and a P-GaN layer 8 sequentially stacked on the substrate 1. Among them, the multi-quantum well layer 6 comprises a shallow well transition layer 61, a high-temperature quantum well layer 62, a stress release layer 63 and a low-temperature quantum well layer 64 stacked in sequence, and the stress release layer 63 comprises an AlN layer 631 and a GaN layer 632 periodically and alternately stacked.
[0032] Among them, the stress release layer 63 is a periodic structure, and each period includes an AlN layer 631 and a GaN layer 632 stacked in sequence. The lattice constant of AlN is relatively small, which means that when the AlN layer 631 is deposited on the GaN layer 632, the AlN layer 631 tends to shrink to adapt to its smaller lattice constant. This shrinkage is restricted by the GaN layer 632 below, thereby generating compressive stress. The compressive stress brought by AlN effectively relieves the tensile stress brought by the growth of GaN. Therefore, adding a stress release layer 63 between the high-temperature quantum well 62 and the low-temperature quantum well layer 64 can effectively reduce the epitaxial defects brought by the high-temperature quantum well layer 62, effectively reduce the GaN epitaxial dislocation density, improve the surface morphology of the GaN epitaxial layer, release the epitaxial stress, and effectively reduce the polarization electric field of the low-temperature quantum well layer 64 grown later, thereby reducing the overflow of electrons under large currents, and improving the luminous efficiency of the light-emitting diode under large currents, that is, reducing the Droop effect of the light-emitting diode.
[0033] Specifically, the number of cycles of the alternating growth of the stress release layer 63 is 2 to 10, and is exemplarily 3, 5, 7, 8 or 9, but not limited thereto. Preferably, the number of cycles of the alternating growth of the stress release layer 63 is 5 to 10, the thickness of the AlN layer 631 is 1 nm to 10 nm, and is exemplarily 2 nm, 4 nm, 5 nm, 6 nm or 8 nm, but not limited thereto, and the thickness of the GaN layer 632 is 1 nm to 10 nm, and is exemplarily 2 nm, 4 nm, 5 nm, 6 nm or 8 nm, but not limited thereto. Preferably, the thickness of the AlN layer 631 is 1 nm to 5 nm, and the thickness of the GaN layer 632 is 1 nm to 5 nm. Based on the stress release layer 63 composed as above, the crystal quality of the epitaxial structure can be further optimized, and the luminous efficiency of the light-emitting diode under high current can be improved.
[0034] In a preferred embodiment, the GaN layer 632 is a Si-doped GaN layer, and the Si doping concentration is 1×10 16 atoms / cm 3 ~1×10 19 atoms / cm 3 , exemplarily 5×10 16 atoms / cm 3 , 1×10 17 atoms / cm 3 , 5×10 17 atoms / cm 3 , 1×10 18 atoms / cm 3 or 5×10 18 atoms / cm 3 The GaN layer 632 is a Si-doped GaN layer, which can provide electrons for the low-temperature quantum well layer 64 , thereby improving the electron-hole recombination efficiency in the low-temperature quantum well layer 64 .
[0035] It is understood that the shallow well transition layer 61, the high temperature quantum well layer 62 and the low temperature quantum well layer 64 can be an InGaN / GaN type quantum well structure or an InGaN / Si doped GaN type quantum well structure, but are not limited thereto. In one embodiment, the shallow well transition layer 61 includes periodically alternately stacked InGaN layers. x Ga 1-x N potential well layer 611 and a first GaN barrier layer 612. The high temperature quantum well layer 62 includes periodically alternately stacked In y Ga 1-y N potential well layer 621 and second GaN barrier layer 622. The low temperature quantum well layer 63 includes In z Ga 1-zN potential well layer 631 and the third GaN barrier layer 632. Among them, 0.01≤x≤y≤z≤0.5. The shallow well transition layer 61 and the high temperature quantum well layer 62 based on the above structure can effectively buffer the compressive strain of the low temperature quantum well layer 64, reduce the polarization electric field strength, and increase the probability of electron-hole recombination. Furthermore, combined with the stress release layer 63 set between the high temperature quantum well layer 61 and the low temperature quantum well layer 64, the epitaxial crystal quality can be further increased and the polarization electric field strength can be reduced. Based on the combination of the above layered structure, the In in the low temperature quantum well layer 64 z Ga 1-z The N potential well layer 641 may use a higher In component (ie, z=0.2-0.5), which effectively solves the Green Gap problem.
[0036] In one embodiment, the number of cycles of the alternating growth of the shallow well transition layer 61 is 1 to 20, exemplarily 5, 8, 10, 15 or 18, but not limited thereto. x Ga 1-x The In component ratio x of the N potential well layer 611 is 0.01-0.1, and is 0.02, 0.04, 0.05, 0.06 or 0.08, but not limited thereto. The thickness is 1 nm-5 nm, and is 1.5 nm, 2 nm, 2.5 nm, 3 nm or 4 nm, but not limited thereto. The first GaN barrier layer 612 is a Si-doped GaN barrier layer, and the Si doping concentration is 5×10 17 atoms / cm 3 ~5×10 19 atoms / cm 3 , exemplarily 7.5×10 17 atoms / cm 3 , 1×10 18 atoms / cm 3 , 5×10 18 atoms / cm 3 ,9×10 18 atoms / cm 3 or 1×10 19 atoms / cm 3 , but not limited thereto, the thickness is 10nm to 50nm, exemplarily 15nm, 20nm, 25nm, 30nm or 40nm, but not limited thereto. Preferably, In x Ga 1-x The thickness of the N potential well layer 611 is 3nm-4nm, and the thickness of the first GaN barrier layer 612 is 30nm-40nm. The shallow well layer 61 can effectively buffer the compressive strain of the low temperature quantum well layer 64, reduce the polarization electric field intensity, improve the electron-hole recombination efficiency, and improve the luminescence efficiency.
[0037] The number of cycles of the alternating growth of the high temperature quantum well layer 62 is 1 to 20, exemplarily 5, 8, 10, 15 or 18, but not limited thereto. y Ga 1-y The In component ratio y of the N potential well layer 621 is 0.1-0.2, and is 0.12, 0.14, 0.15, 0.16 or 0.18, but not limited thereto. The thickness is 1 nm-5 nm, and is 1.5 nm, 2 nm, 2.5 nm, 3 nm or 4 nm, but not limited thereto. The second GaN barrier layer 622 is a Si-doped GaN barrier layer, and the Si doping concentration is 5×10 16 atoms / cm 3 ~5×10 18 atoms / cm 3 , exemplarily 1×10 17 atoms / cm 3 , 5×10 17 atoms / cm 3 , 1×10 18 atoms / cm 3 , 2.5×10 18 atoms / cm 3 or 4×10 18 atoms / cm 3 , but not limited thereto, the thickness is 5nm to 30nm, exemplarily 8nm, 10nm, 15nm, 20nm or 25nm, but not limited thereto. Preferably, In y Ga 1-y The thickness of the N potential well layer 621 is 2 nm to 3 nm, and the thickness of the second GaN barrier layer 622 is 10 nm to 15 nm. y Ga 1-y The N potential well layer 621 is grown at high temperature, has high atomic mobility, is more inclined to two-dimensional material growth, has significantly reduced defects, and is easier to obtain high-quality InGaN materials. y Ga 1-y The proportion of In components in the N potential well layer 621 is lower, and the lattice mismatch stress between the InGaN material and the GaN material is reduced, which significantly improves the quality of the subsequently grown low-temperature quantum well layer 64, thereby improving the luminous efficiency and yield of the LED and other performance.
[0038] The number of cycles of the alternating growth of the low temperature quantum well layer 64 is 6 to 20, and is exemplarily 8, 10, 12, 15 or 18, but is not limited thereto. z Ga 1-zThe In component ratio z of the N potential well layer 641 is 0.2-0.5, and is 0.25, 0.3, 0.35, 0.4 or 0.45, but not limited thereto. The thickness is 2nm-5nm, and is 2.5nm, 3nm, 3.5nm, 4nm or 4.5nm, but not limited thereto. The third GaN barrier layer 642 is a Si-doped GaN barrier layer, and the Si doping concentration is 1×10 17 atoms / cm 3 ~5×10 18 atoms / cm 3 , an exemplary value is 2.5×10 17 atoms / cm 3 , 5×10 17 atoms / cm 3 , 6×10 17 atoms / cm 3 , 7.5×10 17 atoms / cm 3 or 1×10 18 atoms / cm 3 , but not limited thereto, the thickness is 5nm to 20nm, exemplarily 8nm, 10nm, 12nm, 15nm or 18nm, but not limited thereto. Preferably, In z Ga 1-z The thickness of the N well layer 641 is 2 nm to 4 nm, and the thickness of the third GaN barrier layer 642 is 8 nm to 13 nm.
[0039] In a preferred embodiment, the Si doping concentration of the second GaN barrier layer 622 is less than the Si doping concentration of the first GaN barrier layer 612, and the Si doping concentration of the second GaN barrier layer 622 is less than the Si doping concentration of the third GaN barrier layer 632, which can better achieve electron-hole matching in the multi-quantum well layer 6 and avoid electron overflow.
[0040] like Figure 2 As shown, in a preferred embodiment, the GaN-based blue-green light LED epitaxial structure further includes a hole injection layer 9 .
[0041] Specifically, the hole injection layer 9 is disposed between the low-temperature quantum well layer 64 and the electron blocking layer 7. The hole injection layer 9 is a low-temperature P-GaN layer with a thickness of 10 nm to 100 nm, exemplarily 8 nm, 10 nm, 12 nm, 15 nm or 18 nm, but not limited thereto, and a Mg doping concentration of 1×10 18 atoms / cm 3 ~1×10 21 atoms / cm 3 , an exemplary value is 2.5×1017 atoms / cm 3 , 5×10 17 atoms / cm 3 , 6×10 17 atoms / cm 3 , 7.5×10 17 atoms / cm 3 or 9×10 17 atoms / cm 3 The hole injection layer 9 can inject holes into the low-temperature quantum well layer 64 to improve the light-emitting efficiency.
[0042] In a preferred embodiment, the GaN-based blue-green LED epitaxial structure further includes a contact layer 10 .
[0043] Specifically, the contact layer 10 is disposed on the P-GaN layer 8. The contact layer 10 is a heavily doped P-GaN layer with a thickness of 1 nm to 20 nm, exemplarily 8 nm, 10 nm, 12 nm, 15 nm or 18 nm, but not limited thereto, and a Mg doping concentration of 1×10 18 atoms / cm 3 ~1×10 22 atoms / cm 3 , an exemplary value is 2.5×10 17 atoms / cm 3 , 5×10 17 atoms / cm 3 , 6×10 17 atoms / cm 3 , 7.5×10 17 atoms / cm 3 or 9×10 17 atoms / cm 3 The contact layer 10 can optimize the ohmic contact between the epitaxial structure and the LED electrode.
[0044] In addition to the above structure, other layered structures of the present invention are characterized as follows:
[0045] The substrate 1 may be a sapphire substrate, a silicon substrate or a SiC substrate, but is not limited thereto, and is preferably a patterned sapphire substrate.
[0046] The buffer layer 2 may be an AlN layer or an AlGaN layer, but is not limited thereto.
[0047] The 3D layer 3 may be a GaN layer with a thickness of 0.5 μm to 2 μm. The 3D layer 3 may cover the substrate pattern, reduce the dislocation defects at the bottom of the epitaxial structure, release the bottom stress of the epitaxial structure, and thus improve the crystal quality of the epitaxial structure grown subsequently.
[0048] The thickness of the U-GaN layer 4 is 0.5 μm to 2 μm.
[0049] The N-GaN layer 5 may be a Si-doped GaN layer, and the Si doping concentration is 1×10 18 atoms / cm 3 ~1×10 21 atoms / cm 3 , thickness is 0.5μm~1.5μm.
[0050] The electron blocking layer 7 may be a P-AlGaN layer, wherein the Al component ratio is 0.05 to 0.3, the thickness is 20 nm to 130 nm, and the Mg doping concentration is 1×10 18 atoms / cm 3 ~1×10 21 atoms / cm 3 .
[0051] The P-GaN layer 8 may be a Mg-doped GaN layer, and the Mg doping concentration is 5×10 18 atoms / cm 3 ~5×10 20 atoms / cm 3 , thickness is 10nm~150nm.
[0052] Correspondingly, such as Figure 4 As shown, the present invention also discloses a method for preparing a GaN-based blue-green light LED epitaxial structure, which is used to prepare the above-mentioned GaN-based blue-green light LED epitaxial structure, comprising the following steps:
[0053] S1. Provide a substrate 1.
[0054] S2, sequentially growing a buffer layer 2, a 3D layer 3, a U-GaN layer 4, an N-GaN layer 5, a multi-quantum well layer 6, an electron blocking layer 7 and a P-GaN layer 8 on a substrate 1. The epitaxial structure may be grown by MOCVD, MBE, PVD or VPE, but is not limited thereto. Specifically, S2 includes the following steps:
[0055] S21 . Growing a buffer layer 2 on the substrate 1 .
[0056] Specifically, in one embodiment, the buffer layer is an AlN buffer layer and an AlGaN buffer layer stacked in sequence, and the growth of the buffer layer includes the following steps:
[0057] The AlN buffer layer is grown by PVD at a growth temperature of 500°C to 700°C and a power of 2500W to 5000W. During the growth, Ar is used as the sputtering gas and N 2As the precursor, Al as the sputtering target, and then in H 2 Atmosphere or N 2 The treatment is carried out in a vacuum atmosphere at a temperature of 1000°C to 1200°C and a time of 1min to 10min.
[0058] An AlGaN buffer layer is grown on the AlN buffer layer by MOCVD, with a growth temperature of 500° C. to 900° C., a growth pressure of 100 torr to 600 torr, and a V / III ratio of 50 to 1000.
[0059] S22 , growing a 3D layer 3 on the buffer layer 2 .
[0060] Specifically, in one embodiment, the 3D layer is grown by MOCVD, the growth temperature is 700° C. to 950° C., the growth pressure is 100 torr to 400 torr, and the V / III ratio is 800 to 2000.
[0061] S23 , growing a U-GaN layer 4 on the 3D GaN layer 3 .
[0062] Specifically, in one embodiment, the U-GaN layer is grown by MOCVD, the growth temperature is 1050° C. to 1250° C., the growth pressure is 150 torr to 500 torr, and the V / III ratio is 800 to 2500.
[0063] S24 . Growing an N-GaN layer 5 on the U-GaN layer 4 .
[0064] Specifically, in one embodiment, the N-GaN layer is grown by MOCVD, the growth temperature is 1050° C. to 1150° C., the growth pressure is 150 torr to 500 torr, and the V / III ratio is 500 to 2500.
[0065] S25 , growing a multi-quantum well layer 6 on the N-GaN layer 5 .
[0066] Specifically, in one embodiment, the multi-quantum well layer 6 includes a shallow well transition layer 61, a high-temperature quantum well layer 62, a stress release layer 63 and a low-temperature quantum well layer 64 stacked in sequence, and the growth of the multi-quantum well layer 6 includes the following steps:
[0067] S251 , growing a shallow well transition layer 61 on the N-GaN layer 5 .
[0068] Periodic growth of In by MOCVD x Ga 1-x N potential well layer and the first GaN barrier layer until a shallow well transition layer is obtained. x Ga 1-xThe growth temperature of the N potential well layer is 750℃~950℃, the growth pressure is 100torr~500torr, and the V / III ratio is 500~10000; the growth temperature of the first GaN barrier layer is 750℃~950℃, the growth pressure is 100torr~500torr, and the V / III ratio is 500~10000.
[0069] S252 , growing a high-temperature quantum well layer 62 on the shallow well transition layer 61 .
[0070] Periodic growth of In by MOCVD y Ga 1-y N potential well layer and the second GaN barrier layer until a high temperature quantum well layer is obtained. y Ga 1-y The growth temperature of the N potential well layer is 750℃~950℃, the growth pressure is 100torr~500torr, and the V / III ratio is 2000~20000; the growth temperature of the second GaN barrier layer is 750℃~1000℃, the growth pressure is 100torr~500torr, and the V / III ratio is 2000~20000.
[0071] S253 , growing a stress release layer 63 on the high-temperature quantum well layer 62 .
[0072] AlN layer and GaN layer are periodically grown by MOCVD until a stress release layer is obtained. Specifically, the growth temperature is 700℃~950℃, the growth pressure is 100torr~500torr, and the V / III ratio is 2000~20000. In one embodiment, the growth temperature of the AlN layer is 700℃~850℃, the growth pressure is 100torr~500torr, and the V / III ratio is 2000~20000; the growth temperature of the GaN layer is 800℃~950℃, the growth pressure is 100torr~500torr, and the V / III ratio is 2000~20000.
[0073] S254 , growing a low-temperature quantum well layer 64 on the stress release layer 63 .
[0074] Periodic growth of In by MOCVD z Ga 1-z N potential well layer and the third GaN barrier layer until a low temperature quantum well layer is obtained. z Ga 1-z The growth temperature of the N potential well layer is 700℃~850℃, the growth pressure is 100torr~500torr, and the V / III ratio is 2000~20000; the growth temperature of the third GaN barrier layer is 800℃~950℃, the growth pressure is 100torr~500torr, and the V / III ratio is 2000~20000.
[0075] S26 , growing a hole injection layer 9 on the multi-quantum well layer 6 .
[0076] Specifically, in one embodiment, a low-temperature P-GaN layer is grown by MOCVD as a hole injection layer, the growth temperature is 650° C. to 850° C., the growth pressure is 100 torr to 500 torr, and the V / III ratio is 500 to 10,000.
[0077] S27 , growing the electron blocking layer 7 on the hole injection layer 9 .
[0078] Specifically, in one embodiment, a P-AlGaN layer is grown by MOCVD as an electron blocking layer, the growth temperature is 900° C. to 1000° C., the growth pressure is 50 torr to 300 torr, and the V / III ratio is 500 to 10000.
[0079] S28 . Growing a P-GaN layer 8 on the electron blocking layer 7 .
[0080] Specifically, in one embodiment, the P-GaN layer is grown by MOCVD, the growth temperature is 850° C. to 1050° C., the growth pressure is 100 torr to 500 torr, and the V / III ratio is 500 to 3500.
[0081] S29 . Growing a contact layer 10 on the P-GaN layer 8 .
[0082] Specifically, in one embodiment, a heavily doped P-GaN layer is grown by MOCVD as a contact layer, the growth temperature is 650° C. to 950° C., the growth pressure is 100 torr to 500 torr, and the V / III ratio is 10,000 to 20,000.
[0083] In a preferred embodiment, the method further comprises annealing at 600° C. to 900° C. for 3 min to 15 min to obtain a GaN-based blue-green light emitting diode epitaxial structure.
[0084] The present invention will be further described below with specific embodiments:
[0085] Example 1
[0086] This embodiment provides a GaN-based blue-green light LED epitaxial structure, including a substrate and a buffer layer, a 3D layer, a U-GaN layer, an N-GaN layer, a multi-quantum well layer, an electron blocking layer and a P-GaN layer stacked on the substrate in sequence.
[0087] The substrate is a sapphire substrate, and the buffer layer includes an AlN buffer layer and an AlGaN buffer layer stacked on the substrate in sequence. The thickness of the AlN buffer layer is 17nm, and the thickness of the AlGaN buffer layer is 25nm. The 3D layer is a GaN layer with a thickness of 1.5μm, a U-GaN layer with a thickness of 1.5μm, and a N-GaN layer with a thickness of 2μm. The Si doping concentration is 5.5×10 19 atoms / cm 3 .
[0088] The multi-quantum well layer includes a shallow well transition layer, a high-temperature quantum well layer, a stress release layer and a low-temperature quantum well layer which are stacked in sequence.
[0089] The shallow well transition layer is a periodic structure with 3 periods. Each period includes In 0.1 Ga 0.9 N potential well layer and the first GaN barrier layer, In 0.1 Ga 0.9 The thickness of the N well layer is 3.5 nm, the thickness of the first GaN barrier layer is 35 nm, and the Si doping concentration is 7.5×10 17 atoms / cm 3 .
[0090] The high temperature quantum well layer is a periodic structure with 6 periods. Each period includes In 0.2 Ga 0.8 N potential well layer and the second GaN barrier layer, In 0.2 Ga 0.8 The thickness of the N potential well layer is 2 nm, the thickness of the second GaN barrier layer is 10 nm, and the Si doping concentration is 1×10 17 atoms / cm 3 .
[0091] The stress release layer is a periodic structure with a period number of 5, and each period includes an AlN layer and a GaN layer stacked in sequence. The thickness of the AlN layer is 1 nm, and the thickness of the GaN layer is 1 nm.
[0092] The low-temperature quantum well layer is a periodic structure with 10 periods. Each period includes sequentially stacked In 0.25 Ga 0.75 N potential well layer and the third GaN barrier layer, In 0.25 Ga 0.75 The thickness of the N potential well layer is 3.5 nm, the thickness of the third GaN barrier layer is 11 nm, and the Si doping concentration is 5×10 17 atoms / cm 3 .
[0093] The electron blocking layer is a P-AlGaN layer with an Al component ratio of 0.25, a thickness of 35 nm, and a Mg doping concentration of 1.3×10 18 atoms / cm 3 .
[0094] The thickness of the P-GaN layer is 20 nm, and the Mg doping concentration is 3.2×10 19 atoms / cm 3 .
[0095] The preparation method of the GaN-based blue-green LED epitaxial structure in this embodiment is as follows:
[0096] (1) Provide a substrate.
[0097] (2) PVD was used to grow the AlN buffer layer on the substrate at a growth temperature of 540°C and a power of 4300 W. During the growth, Ar was used as the sputtering gas and N 2 As the precursor, Al is used as the sputtering target. After the growth is completed, the substrate is loaded into the MOCVD machine and 2 The AlGaN buffer layer was grown at 750°C, 400 torr, and a V / III ratio of 250.
[0098] (3) The 3D layer was grown at 900°C, 200 torr, and a V / III ratio of 800.
[0099] (4) The U-GaN layer was grown at 1150°C, 300 torr, and a V / III ratio of 1000.
[0100] (5) Grow an N-GaN layer at 1100°C, 300 torr, and a V / III ratio of 1000.
[0101] (6) In was grown at 900°C, 300 torr, and a V / III ratio of 10,000. 0.1 Ga 0.9 N potential well layer, and then the first GaN barrier layer is grown at 900°C, 300torr, and a V / III ratio of 10000, and the periodic growth is repeated for 3 cycles.
[0102] In was grown at 800°C, 300 torr, and a V / III ratio of 10,000. 0.15 Ga 0.85 N potential well layer, and then grow a second GaN barrier layer at 850°C, 300 torr, and a V / III ratio of 10000, and repeat the periodic growth for 6 cycles.
[0103] An AlN layer was grown under the conditions of 800° C., 300 torr, and a V / III ratio of 10,000, and then a GaN layer was grown under the conditions of 800° C., 300 torr, and a V / III ratio of 10,000, and the periodic growth was repeated for 5 cycles.
[0104] In was grown at 780°C, 300 torr, and a V / III ratio of 10,000. 0.2 Ga 0.8 N potential well layer, and then grow a third GaN barrier layer under the conditions of 900°C, 300torr, and a V / III ratio of 10000, and repeat the periodic growth for 10 cycles.
[0105] (7) Grow a P-AlGaN layer at 900°C, 200 torr, and a V / III ratio of 800.
[0106] (8) A P-GaN layer is grown at 950°C, 300 torr, and a V / III ratio of 1200, and then annealed at 800°C for 5 minutes.
[0107] Example 2
[0108] This embodiment provides a GaN-based blue-green LED epitaxial structure, which is different from the embodiment 1 in that the GaN layer in the stress release layer is a Si-doped GaN layer with a Si doping concentration of 2×10 18 atoms / cm 3 The rest are the same as in Example 1.
[0109] Example 3
[0110] This embodiment provides a GaN-based blue-green LED epitaxial structure, which differs from the embodiment 2 in that it also includes a hole injection layer and a contact layer. The hole injection layer is arranged between the multi-quantum well layer and the electron blocking layer. The hole injection layer is a low-temperature P-GaN layer with a thickness of 50nm and a Mg doping concentration of 5.5×10 18 atoms / cm 3 The contact layer is set on the P GaN layer with a thickness of 8nm and a Mg doping concentration of 6.8×10 20 atoms / cm 3 Correspondingly, the preparation method of the hole injection layer is: growing the hole injection layer under the conditions of 700°C, 200 torr, and a V / III ratio of 800. The preparation method of the contact layer is: growing the contact layer under the conditions of 780°C, 300 torr, and a V / III ratio of 15000. The rest is the same as in Example 1.
[0111] Comparative Example 1
[0112] This comparative example provides a GaN-based blue-green LED epitaxial structure, which differs from Example 1 in that no stress release layer is provided between the high-temperature quantum well layer and the low-temperature quantum well layer. Accordingly, the preparation method does not include the preparation of the stress release layer. The rest is the same as Example 2.
[0113] Comparative Example 2
[0114] This comparative example provides a GaN-based blue-green LED epitaxial structure, which is different from Example 1 in that the stress release layer is an AlGaN layer, the Al component accounts for 0.2, and the thickness is 10nm. Correspondingly, the preparation method of the stress release layer is: growing the stress release layer under the conditions of 800°C, 300torr, and V / III ratio of 10000. The rest is the same as Example 1.
[0115] The epitaxial structures obtained in Examples 1 to 3, Comparative Examples 1 and 2 were prepared into 55mil×55mil flip-chip chips, which were lit at test currents of 700mA, 1400mA, 2100mA, and 3000mA, respectively, to test their luminous intensity. The specific results are shown in the following table:
[0116]
[0117] The above is a preferred embodiment of the invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the invention. These improvements and modifications are also considered to be within the scope of protection of the invention.
Claims
1. A GaN-based blue-green LED epitaxial structure, characterized in that: It includes a substrate and a buffer layer, a 3D layer, a U-GaN layer, an N-GaN layer, a multi-quantum well layer, an electron blocking layer and a P-GaN layer stacked in sequence on the substrate; wherein the multi-quantum well layer includes a shallow well transition layer, a high-temperature quantum well layer, a stress release layer and a low-temperature quantum well layer stacked in sequence, and the stress release layer includes AlN layers and GaN layers stacked alternately in a periodic manner.
2. The GaN-based blue-green LED epitaxial structure according to claim 1, characterized in that: The number of cycles of the alternating growth of the stress release layer is 2 to 10, the thickness of the AlN layer is 1 nm to 10 nm, and the thickness of the GaN layer is 1 nm to 10 nm.
3. The GaN-based blue-green LED epitaxial structure according to claim 1, characterized in that: The GaN layer is a Si-doped GaN layer, and the Si doping concentration is 1×10 16 atoms / cm 3 ~1×10 19 atoms / cm 3 .
4. The GaN-based blue-green LED epitaxial structure according to claim 1, characterized in that: The shallow well transition layer includes periodically alternately stacked In x Ga 1-x N potential well layer and a first GaN barrier layer; the high temperature quantum well layer includes periodically alternately stacked In y Ga 1-y N potential well layer and a second GaN barrier layer; the low temperature quantum well layer comprises periodically alternately stacked In z Ga 1-z N potential well layer and a third GaN barrier layer; wherein 0.01≤x≤y≤z≤0.
5.
5. The GaN-based blue-green LED epitaxial structure according to claim 1, characterized in that: The number of cycles of the alternating growth of the shallow well transition layer is 1 to 20. x Ga 1-x The In component ratio x of the N potential well layer is 0.01-0.1, and the thickness is 1nm-5nm. The first GaN barrier layer is a Si-doped GaN barrier layer, and the Si doping concentration is 5×10 17 atoms / cm 3 ~5×10 19 atoms / cm 3 , thickness is 10nm~50nm; The number of cycles of the alternating growth of the high temperature quantum well layer is 1 to 20. y Ga 1-y The In component ratio y of the N potential well layer is 0.1-0.2, and the thickness is 1nm-5nm. The second GaN barrier layer is a Si-doped GaN barrier layer, and the Si doping concentration is 5×10 16 atoms / cm 3 ~5×10 18 atoms / cm 3 , thickness is 5nm~30nm; The number of cycles of the alternating growth of the low temperature quantum well layer is 6 to 20. z Ga 1-z The In component ratio z of the N potential well layer is 0.2-0.5, and the thickness is 2nm-5nm. The third GaN barrier layer is a Si-doped GaN barrier layer, and the Si doping concentration is 1×10 17 atoms / cm 3 ~5×10 18 atoms / cm 3 , thickness is 5nm~20nm.
6. The GaN-based blue-green LED epitaxial structure according to claim 1, characterized in that: Also includes a hole injection layer and / or a contact layer; The hole injection layer is arranged between the low-temperature quantum well layer and the electron blocking layer; the hole injection layer is a low-temperature P-GaN layer with a thickness of 10nm to 100nm and a Mg doping concentration of 1×10 18 atoms / cm 3 ~1×10 21 atoms / cm 3 ; The contact layer is disposed on the P-GaN layer; the contact layer is a heavily doped P-GaN layer with a thickness of 1nm to 20nm and a Mg doping concentration of 1×10 18 atoms / cm 3 ~1×10 22 atoms / cm 3 .
7. A method for preparing a GaN-based blue-green light LED epitaxial structure, used for preparing the GaN-based blue-green light LED epitaxial structure as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: Providing a substrate, and sequentially growing a buffer layer, a 3D layer, a U-GaN layer, an N-GaN layer, a multi-quantum well layer, an electron blocking layer, and a P-GaN layer on the substrate; The multi-quantum well layer comprises a shallow well transition layer, a high-temperature quantum well layer, a stress release layer and a low-temperature quantum well layer stacked in sequence, and the stress release layer comprises an AlN layer and a GaN layer stacked alternately in a periodic manner.
8. The method for preparing a GaN-based blue-green LED epitaxial structure according to claim 7, characterized in that: The growth temperature of the stress release layer is 700° C. to 950° C., the growth pressure is 100 torr to 500 torr, and the V / III ratio is 2000 to 20000.
9. The method for preparing a GaN-based blue-green LED epitaxial structure according to claim 7, characterized in that: The preparation method of the shallow well transition layer comprises periodically alternatingly growing In x Ga 1-x N potential well layer and the first GaN barrier layer, the In x Ga 1-x The growth temperature of the N potential well layer is 750° C. to 950° C., the growth pressure is 100 torr to 500 torr, and the V / III ratio is 500 to 10000; the growth temperature of the first GaN barrier layer is 750° C. to 950° C., the growth pressure is 100 torr to 500 torr, and the V / III ratio is 500 to 10000; The preparation method of the high temperature quantum well layer comprises periodically alternatingly growing In y Ga 1-y N potential well layer and the second GaN barrier layer, the In y Ga 1-y The growth temperature of the N potential well layer is 750° C. to 950° C., the growth pressure is 100 torr to 500 torr, and the V / III ratio is 2000 to 20000; the growth temperature of the second GaN barrier layer is 750° C. to 1000° C., the growth pressure is 100 torr to 500 torr, and the V / III ratio is 2000 to 20000; The preparation method of the low temperature quantum well layer comprises periodically alternatingly growing In z Ga 1-z N potential well layer and the third GaN barrier layer, the In z Ga 1-z The growth temperature of the N potential well layer is 700℃~850℃, the growth pressure is 100torr~500torr, and the V / III ratio is 2000~20000; the growth temperature of the third GaN barrier layer is 800℃~950℃, the growth pressure is 100torr~500torr, and the V / III ratio is 2000~20000.
10. The method for preparing a GaN-based blue-green LED epitaxial structure according to claim 7, characterized in that: It also includes growing a hole injection layer between the multi-quantum well layer and the electron blocking layer, and / or growing a contact layer on the P-GaN layer; The hole injection layer has a growth temperature of 650°C to 850°C, a growth pressure of 100 torr to 500 torr, and a V / III ratio of 500 to 10000; The growth temperature of the contact layer is 650° C. to 950° C., the growth pressure is 100 torr to 500 torr, and the V / III ratio is 10,000 to 20,000.
Citation Information
Cited By
Miniature light emitting diode and preparation method thereof
CN121038453A
Blue-green double-wave epitaxial structure and growth method thereof
CN121665781A
GaN-based blue-green light LED epitaxial structure and preparation method thereof, and GaN-based blue-green light LED
CN121665788A